2020
DOI: 10.1186/s12894-020-00725-z
|View full text |Cite|
|
Sign up to set email alerts
|

Sperm parameters and anti-Müllerian hormone remain stable with Helicobacter pylori infection: a cross-sectional study

Abstract: Background and aims It has been reported that Helicobacter pylori (HP) infection was more prevalent in infertile populations. HP infection could lead to decreased sperm parameters, and treating the HP infection could improve the quality of sperm. However, studies investigating the relationship between infertility and HP infection are still limited, and more evidence is required. Therefore, we performed the present study to investigate the impact of HP infection on sperm quality in males and on ovarian reserve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Some immunocytochemical studies emphasized that serum samples from infected men (as well as anti- H. pylori hyperimmune serum) reacted with the equatorial segment and the flagella (especially abundant in tubulin) of sperm ( Figura et al, 2002 ). However, in 2020, a cross-sectional study found that there was no difference in anti-Müllerian hormone (AMH) levels and sperm parameters in Chinese patients based on H. pylori infection history ( Feng et al, 2020 ).…”
Section: Reproductive Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Some immunocytochemical studies emphasized that serum samples from infected men (as well as anti- H. pylori hyperimmune serum) reacted with the equatorial segment and the flagella (especially abundant in tubulin) of sperm ( Figura et al, 2002 ). However, in 2020, a cross-sectional study found that there was no difference in anti-Müllerian hormone (AMH) levels and sperm parameters in Chinese patients based on H. pylori infection history ( Feng et al, 2020 ).…”
Section: Reproductive Diseasementioning
confidence: 99%
“…A meta-analysis of 15 articles that included 3,046 cases showed that H. pylori was positively correlated with HT and GD (HT: 95% CI: 1.44-3.23, OR = 2.16; GD: 95% CI: 1.68-4.61, OR = 2.78), and CagA+ H. pylori was positively related to AITD (95% CI: 1.07-3.70, OR = 1.99) (Hou et al, 2017). Nevertheless, another study proposed that this pathogenesis might be caused by molecular mimics and an increased inflammatory state (Figura et al, 2019; Supplementary Table S3).…”
Section: Endocrine and Metabolic Diseasementioning
confidence: 99%
“…Secretion peaks during foetal life until puberty and declines to low levels after adulthood. It is mainly involved in the regulation of cell differentiation and accelerates degenerate mullerian in male embryos [12][13][14]. Data have shown that AMH can play a regulatory function during sperm generation and promote sperm formation [15][16][17].…”
Section: Introductionmentioning
confidence: 99%